Effects of using code-switching for teaching and learning of English as a second language in a multilingual environment - Mohammed, Kolo Baba; Hamzah, Nurul Huda; Shangeetha, R.K. (Universitas Syiah Kuala, 2025)
The influence of code-switching on ESL teachers and students in a multilingual setting is regarded as one of the causes of poor learning and grammatical errors in English in Nigeria. This study investigated the effect of code-switching on English language instruction and learning in a multilingual region of Northern Nigeria. The primary objective of this study was to investigate the impact of code-switching on the instruction and learning of English by the ESL students in a multilingual region of Northern Nigeria. Myers-Scottons Markedness Model theory and quantitative technique were utilized. A questionnaire was used for data collection, and descriptive statistics were employed to analyse the demographic and questionnaire items using frequency distributions, means, and tables. Responses were expressed in percentages. The students from the Nigerian Certificate in Education programme participated in the study. The findings showed that the teachers and students employed code-switching in the classroom, and it had both positive and negative consequences. The results revealed that code-switching facilitated comprehension of lessons for the students with limited English abilities and eased the workload of the teachers, among other benefits. However, it had adverse effects on the students use of English at the tertiary level of education, as it affected their reading and writing abilities and proficiency. The study suggests that ESL teachers, policymakers, and researchers tailor their instructional approaches by considering students linguistic abilities, cultural backgrounds, and educational outcomes, which encourages the students use of the English language to improve their proficiency.